(untitled) (Research, Society and Development, 2022)
Background: The administration of carbohydrate solution has gained prominence in recent years as part of fasting abbreviation protocols and improvement in patient care and recovery. The ERAS protocol (Enhanced Recovery after Surgery) has gained prominence as one of the processes that preloads carbohydrates is used as part of the approach for better perioperative outcome. Aims: Review and discuss data on the effects of preoperative carbohydrate solutions on parameters related to macronutrients metabolism. Furthermore, specific metabolic outcomes such as insulin resistance, adipocytokine levels and quality parameters such as length of stay and postoperative complications were also analyzed. Methods: A literature review was developed using the following descriptors: Oral carbohydrate, Carbohydrate loading, Preoperative. The variables analyzed were insulin sensitivity, adipocytokine levels, blood glucose, insulin, ketone bodies and free fatty acids, in addition to postoperative outcomes such as length of stay, opioid consumption, nausea and vomiting, and wound infection. Results: The search resulted in nine papers for the composition of results, one meta-analysis, and eight randomized controlled trials. Increasingly robust evidence strengthens the effect of preoperative carbohydrate solution as an important intervention to decrease insulin resistance and catabolic effects triggered by preoperative fasting and the stress of surgical trauma, as well as improvement in clinical parameters. Conclusions: Carbohydrate preload is a robust intervention to improve perioperative metabolic parameters, and more studies are needed to define the most benefited populations and better form of administration.